2021
DOI: 10.3390/su13169422
|View full text |Cite
|
Sign up to set email alerts
|

Environment, Identity, and Response to Polluted Landscapes

Abstract: Research indicates that beautiful nature can have positive impacts. Does polluted nature have a corresponding negative impact? This paper presents two experiments investigating the impact of viewing images of natural settings, on a college campus, that do or do not contain litter. The moderating role of environmental identity was also examined. Study 1 showed that landscapes with litter evoked more negative emotions among a sample of 332 U.S. residents on MTurk than did landscapes without litter. Surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…We found that viewers with higher levels of connectedness to nature found the images more pleasant, more beautiful, and they evoked enhanced aesthetic emotions. This finding adds to a growing body of work showing that the trait of connectedness to nature influences perceptual and emotional responses to natural scenes ( Berto et al, 2018 ; Clayton, 2021 ; Davis & Gatersleben, 2013 ; McMahan et al, 2018 ; Tang, Sullivan & Chang, 2015 ), but extends our understanding of this association by investigating several specifically aesthetic responses, namely pleasure, beauty and aesthetic emotion. The positive association between connectedness to nature and participants’ aesthetic responses to the images of nature is consistent with theories of aesthetic experience which emphasise the importance of the psychological resonance between the viewer and the content of the image (see e.g ., Berleant, 1992 ).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…We found that viewers with higher levels of connectedness to nature found the images more pleasant, more beautiful, and they evoked enhanced aesthetic emotions. This finding adds to a growing body of work showing that the trait of connectedness to nature influences perceptual and emotional responses to natural scenes ( Berto et al, 2018 ; Clayton, 2021 ; Davis & Gatersleben, 2013 ; McMahan et al, 2018 ; Tang, Sullivan & Chang, 2015 ), but extends our understanding of this association by investigating several specifically aesthetic responses, namely pleasure, beauty and aesthetic emotion. The positive association between connectedness to nature and participants’ aesthetic responses to the images of nature is consistent with theories of aesthetic experience which emphasise the importance of the psychological resonance between the viewer and the content of the image (see e.g ., Berleant, 1992 ).…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, increased attention to natural scenes in individuals high in connectedness to nature may also explain the enhanced negative responses to viewing scenes of degraded landscapes by these types of individuals as reported in the study by Clayton (2021) . It would be worthwhile in future studies to investigate the amount of attention paid to nature scenes and its influence on the evaluation of the scene using more implicit indices of attention, such as eye-tracking metrics which could address additional questions about the nature of the enhanced attention to the scenes, for example whether enhanced attention is reflected only in increased viewing times, or if it is also associated with increased spatial exploration of the scene.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, it also affects the perception of natural environments. Clayton (2021) [49], for example, showed that different relationships with nature can also affect the emotional well-being in certain landscapes. Being in nature can increase your commitment to the landscape and can lead to a less superficial evaluation of the respective landscape [50].…”
Section: Introductionmentioning
confidence: 99%